Exploring the representation of social justice in the Ghanaian curriculum - Owusu-Ansah, Nana Akosua; Anku, Joyce; Annan-Brew, Ruth Keziah; Boahene, Akwasi Addae (Intelektual Pustaka Media Utama, 2026)
This study presents a content analysis of Ghana’s English and mathematics curricula. The aim was to determine if the content in both curricula creates awareness of social injustice issues. It was a qualitative study, and data was collected from the official curricula. The study found that the content in the curricula makes a good attempt to represent gender equally in the roles assigned to both genders. However, the content does not create awareness of the availability, accessibility, and distribution of resources. The concepts and examples of socioeconomic issues need to reflect the realities satisfactorily. It was recommended that a conscious effort be made to integrate issues of social injustice in the English and mathematics curricula in the next curricula for the pre-tertiary level.